Drivers of pH increase and implications for low salinity effect in sandstone. (15th April 2018) - Chen, Yongqiang; Xie, Quan; Pu, Wanfen; Saeedi, Ali
Graphical abstract: LS means low salinity water; HS means high salinity water. B14, B15, B16 and B10 are the labels of experimental core plugs (Table 3) for coreflooding experiments conducted by RezaeiDoust et al. (Energy & Fuels. 2011; 25(5):2151–62.) Highlights: Multi-component ion exchange leads to a pH increase during low salinity flooding. Basal-charged clays prompt a pH increase during low salinity flooding. Low salinity flooding may be applied in reservoirs rich in basal-charged clays. Abstract: Low salinity water flooding appears to be a cost-effective and environmentally friendly means to shift wettability of oil/brine/rock system towards more water-wet, thus improving hydrocarbon recovery. While the contribution of kaolinite (edge-charged clays) on low salinity effect has been extensively investigated, how basal-charged clays (e.g., illite, smectite, and chlorite) contributing to the low salinity effect remains unclear. We thus hypothesize that low salinity water facilitates ion exchange in the presence of basal charged clays, thus lifting off oil films from pore surfaces. To test the hypothesis, we performed a geochemical study using PHREEQC in light of double layer diffuse theory. We quantitatively interpreted the pH increase and low salinity effect from corefloods conducted by RezaeiDoust et al. [RezaeiDoust A, Puntervold T, Austad T. Chemical verification of the EOR mechanism by using low saline/smart water in sandstone. Energy & Fuels. 2011;25(5):2151–62.]. We demonstrate that low salinity water triggers a pH increase at the presence of basal-charged clays, thus a more water-wet because of ion exchange. We therefore expand the application envelope of low salinity water flooding to reservoirs with basal-charged clays.